c.1 - Jhabuala, Noshirvan H. (Bombay, 1989)
Jurisprudence deals with law from a philosophical point of view, and is therefore sometimes described as an abstract subject which is difficult to grasp. This is, however, a misconception. No doubt the student will find this subject more "abstract" than say, the law of contracts or the law of torts. Nevertheless, jurisprudence does have a practical application, inasmuch as it may be said to be the foundation of all branches of law
Keywords: Jurisprudence